Fasting Plasma Glucose Increase and Neutrophil-to-Lymphocyte Ratio as Risk Predictors of Clinical Outcome of COVID-19 Pneumonia in Type 2 Diabetes Mellitus - Petrakis, Vasilios; Panagopoulos, Periklis; Trypsianis, Grigorios; Papazoglou, Dimitrios; Papanas, Nikolaos (Experimental and Clinical Endocrinology & Diabetes, 2023)
Aim of the study To evaluate fasting plasma glucose (FPG) increase and neutrophil-to-lymphocyte ratio (NLR) as risk predictors of severe clinical outcome of COVID-19 pneumonia in type 2 diabetes mellitus (T2DM) hospitalised patients.Patients and methods Type 2 diabetes mellitus (T2DM) patients hospitalised between March 2020 and February 2021 were studied retrospectively. The NLR ratio at admission and FPG increase (day 7, day with maximal FPG) were evaluated in association with the clinical progression of SARS-CoV-2 infection.Results Three hundred patients (165 men, 135 women) were included in the study. The mean age was 67.17±8.65 years. Severe COVID-19 pneumonia was diagnosed in 170 patients (56.7%). Fifty-four patients (18%) were intubated and 49 (16.3%) died. Greater increase in FPG (79.5 vs. 44.5 mg/dL for day 1–7, p<0.001; and 113.5 vs. 75 mg/dL for day 1-day with maximum glucose value, p<0.001) and higher NLR at admission (10.65 vs. 6.85) were seen in patients with need of high-flow oxygen compared to those without need, and they were associated with a higher probability of intubation and death.Conclusion FPG increase and NLR could be significant risk predictors of severe COVID-19 pneumonia in T2DM hospitalised patients.
Keywords: SARS-CoV-2; COVID-19; diabetes mellitus; hyperglycaemia; NLR